Management of connective tissue disease-associated interstitial lung disease - Keerthi Talari (Indian Journal of Rheumatology)
The management of connective tissue diseases (CTD)-associated interstitial lung disease (ILD) is challenging considering its myriad presentations and variable course. Evidence to guide treatment is insufficient with very few randomized trials reported till date. This review discusses the current evidence guiding management of CTD-ILD with a specific focus on corticosteroids, cyclophosphamide, mycophenolate, azathioprine, calcineurin inhibitors, and pirfenidone. Corticosteroids (except in systemic sclerosis [SSc]-ILD) in combination with immunosuppressants form the mainstay of therapy in CTD-ILD. Cyclophosphamide and mycophenolate mofetil are backed by randomised trials-Scleroderma lung study I and II respectively for SSc-ILD, while calcineurin inhibitors with or without cyclophosphamide have emerged as a promising initial therapy in myositis associated ILD. Rituximab is probably beneficial for all forms of CTD-ILD even as randomized trial data are awaited. General measures such as lifestyle modification, pulmonary rehabilitation, vaccination, prophylaxis, supplemental oxygen, palliative care are also of paramount importance. Future research should focus on long-term efficacy, safety and head-to-head comparison of drugs, role of upfront combination therapies, supportive and palliative care.